Medroxyprogesterone acetate attenuates demyelination, modulating microglia activation in a cuprizone neurotoxic demyelinating mouse model - Mohammadi, Maryam; Abdi, Mahdad; Alidadi, Mehdi; Mohamed, Wael Mohamed Yousef; Zibara, Kazem; Kashani, Iraj Ragerdi (e-Century Publishing Corporation, 2021)
: Clinical data reported a reduction of Multiple sclerosis (MS) symptoms during pregnancy when progesterone levels are high. Medroxyprogesterone acetate (MPA) is a synthetic progestin contraceptive with unknown neuroprotective effects. This study investigated the effect of a contraceptive dose of MPA on microglia polarization and neuroinflammation in the neurotoxic cuprizone (CPZ)-induced demyelinating mouse model of MS. Mice received 1 mg of MPA weekly, achieving similar serum concentrations in human contraceptive users. Results revealed that MPA therapy significantly reduced the demyelination in the corpus callosum. In addition, MPA treatment induced a significant reduction in microglia M1-markers (iNOS, IL-1β and TNF-α) while M2-markers (Arg-1, IL-10 and TGF-β) were significantly increased. Moreover, MPA resulted in a significant decrease in the number of iNOS positive cells (M1), whereas TREM-2 positive cells (M2) significantly increased. Furthermore, MPA decreased the protein expression levels of NF-κB and NLRP3 inflammasome as well as mRNA expression levels of the downstream product IL-18. In summary, MPA reduces the level of demyelination and has an anti-inflammatory role in CNS demyelination by inducing M2 microglia polarization and suppressing the M1 phenotype through the inhibition of NF-κB and NLRP3 inflammasome. Our results suggest that MPA should be a suitable contraceptive pharmacological agent in demyelinating diseases.